2010
DOI: 10.1080/02678292.2010.517572
|View full text |Cite
|
Sign up to set email alerts
|

Tunable optical and nonlinear optical response of smectic glasses based on cobalt alkanoates

Abstract: The nonlinear optical response of anisotropic smectic glasses based on cobalt alkanoates has been studied using dynamic holography. Laser-dynamic gratings induced by the action of nanosecond laser pulses were observed and analysed for such materials. It was found that the cubic optical nonlinearity of all the anisotropic glasses studied had an electronic origin in the nanosecond range, caused by nonlinear polarisation of the cobalt alkanoate complexes. Fundamental optical (refractive index and absorption coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The following types of chemical compounds were used in the studies of nonlinear-optical properties: As was shown in our previous works, all studied materials form the liquid crystal state (Smectic A) [11,12] under melting. It should be noted that the abovementioned liquid crystalline materials can be easy vitrified under cooling.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following types of chemical compounds were used in the studies of nonlinear-optical properties: As was shown in our previous works, all studied materials form the liquid crystal state (Smectic A) [11,12] under melting. It should be noted that the abovementioned liquid crystalline materials can be easy vitrified under cooling.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the abovementioned liquid crystalline materials can be easy vitrified under cooling. Such a vitrified state can be considered as the "frozen" liquid crystal state and is stable for a long time at room temperature (in fact, samples are still in the glass state even after 1 year after their preparation) [12]. For this reason, the studied glasses are anisotropic and can be called "mesomorphic glasses" in contrast to the well-known isotropic glasses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesogenic sodium, potassium, and thallium(I) octanoates have unlimited solubility in cobalt(II) octanoate mesophase in accordance with the ionic mesogenicity rule, and nonmesogenic lithium octanoate is only partly soluble in it. When studying the phase behaviour of binary systems based on cobalt(II) octanoate with alkali metal and thallium(I) octanoates, formation of optically anisotropic mesomorphic glasses has been established; these glasses absorb light in the visible wavelength range [18], making it possible to use them as universal liquid crystalline matrices in the creation of novel photorefractive and nonlinear optical liquid crystalline materials.…”
Section: Discussionmentioning
confidence: 99%
“…1). The cells were filled with studied liquid crystalline materials at a hot plate at temperature > C−LC ( C−LC is the temperature of the "crystal-liquid crystal" phase transition), by using the capillary technique [17,18]. To prevent the "absorption" of water in the sample, the cell edges were sealed with glue.…”
Section: Cell Preparationmentioning
confidence: 99%